Lattice dynamics from force-fields as a technique for mineral physics - Gale, Julian; Wright, Kathleen (Geochemistry Society Mineralogical Society of America, 2010)
Theory and computation play an increasingly important role in the field of mineral physics by allowing the scientist to probe environments, such as the deep Earth, that are challenging or impossible to access extensively by experiment. Quantum mechanical methods are often the technique of choice, usually based on Kohn-Sham density functional theory as the computationally most practical approach for solids. Although calculations at this level can already be performed on thousands of atoms (Soler et al. 2002; Cankurtaran et al. 2008), the ability to sample nuclear configuration space is often restricted. While density functional theory is typically considered the defacto standard, it is important to remember that with current functionals the results will typically be quantitatively in error with respect to experiment, with occasional qualitative errors (Bilic and Gale 2009). The strength of the method is that the errors are generally systematic and can be anticipated a priori.